Biomaterials for bone infections: antibacterial mechanisms and immunomodulatory effects - Haoran Wang; Hongxia Li; Shengnan Jin; Fang Yan; Xiaoyu Qu; Xi Chen; Zishan Peng; Linping Wang; Junying Li; Yang Liu; Yang Liu (Frontiers in Cellular and Infection Microbiology)
As the global population continues to age, an increasing number of individuals suffer from osteoporosis, fractures, bone infections, and bone tumors. Among these, bone infection is considered one of the most challenging clinical infections due to its high recurrence rate, bacterial resistance, high incidence, and substantial treatment costs. However, these challenges underscore the urgent need for clinicians to develop novel therapeutic strategies to improve the current cure rate and reduce the mortality associated with bone infections. Current scientific research on bone infections primarily focuses on developing new antibacterial targets and infection-resistant biomaterials. In recent years, remarkable advancements have been made in anti-infective biomaterials, offering promising solutions to overcome bone infections. By optimizing the biological properties of biomaterials or integrating them with other materials, researchers aim to achieve maximum antibacterial efficacy and biocompatibility. Such advancements enhance the integration of biomaterials with soft tissues, improve interactions between bone cells and biomaterials, promote osteogenesis, and mitigate inflammatory responses. This review primarily focuses on exploring the antibacterial mechanisms of infection-resistant biomaterials and their regulatory effects on the immune system, with particular emphasis on nanoscale carriers, scaffolds, and particulate materials.